Bangkit Bersama Masyarakat Desa Sanda Membangun Kesehatan, Ekonomi, Dan Pendidikan Di Masa Pandemi Covid-19: Bangkit Bersama Masyarakat Desa Sanda Membangun Kesehatan, Ekonomi, Dan Pendidikan Di Masa Pandemi Covid-19 - Saraswati, Suprabadevi; Wija Negara, I Ketut; Wulandari Suryaningtyas, Endang (Jurnal Pengabdian Perikanan Indonesia, 2025)
Sanda Village is a coffee producer which is the main priority of this area because the location of this village is suitable for cultivating coffee plants. There are also other commodities such as: chocolate, coconut, durian, banana, cloves, and others. The north of this village is a forest area, so people there usually go to the forest to collect firewood. There are also rice fields in this village. During the Covid-19 pandemic, Sanda Village was very obedient in implementing health protocols. This is proven by the appreciation and award from the Pupuan Police Chief for the cooperation and loyalty of the community to make Sanda Village zero Covid-19. This is a form of effort by Bhabinkamtimbas and the Village Head, Prajuru and the Sanda Village Covid Task Force in preventing the spread of the Covid-19 chain will receive assistance in the form of ideas and energy in developing and carrying out future development. This can be realized because through the Thematic KKN activity, in addition to students moving to improve soft skills and hard skills, students are also required to socialize and empathize with the conditions of the residents of Sanda Village, Pupuan District, Tabanan Regency.